Tropical Forests - Ecology, Diversity and Conservation Status 2023
DOI: 10.5772/intechopen.109070
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Traditional African Vegetables Agrobiodiversity – Livelihood Utilization and Conservation in Tanzania Rural Communities

Abstract: The agricultural sector is challenged to fulfill the nutritional requirements of ever-increasing population. Rates of growth in crop productivity have declined, among many reasons is due to climate change and the decline of water and land resources. Dependence by 50% on few cereal crops like wheat, maize and rice for total food intake and calorie requirements has countersigned loss of biodiversity and decline in crop productivity. The genetic diversity of traditional crop varieties offers resilience to environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…To investigate how local fruit growers are adapting and mitigating the effects of climate change, a thorough analysis is needed. Studies have shown that the agricultural sector in various regions, including Tuban City in Indonesia [9], Tanzania [10], Nepal [11], and Samar in the Philippines [12], have explored alternative crops, conservation of genetic resources, and farming strategies to improve sustainability, resilience, and profitability. These studies provide valuable insights into the potential of underutilized crops, the importance of genetic diversity, and the impact of farming practices on profit optimization.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate how local fruit growers are adapting and mitigating the effects of climate change, a thorough analysis is needed. Studies have shown that the agricultural sector in various regions, including Tuban City in Indonesia [9], Tanzania [10], Nepal [11], and Samar in the Philippines [12], have explored alternative crops, conservation of genetic resources, and farming strategies to improve sustainability, resilience, and profitability. These studies provide valuable insights into the potential of underutilized crops, the importance of genetic diversity, and the impact of farming practices on profit optimization.…”
Section: Introductionmentioning
confidence: 99%